4(-7a+2)+10=-6+8a

Simple and best practice solution for 4(-7a+2)+10=-6+8a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-7a+2)+10=-6+8a equation:


Simplifying
4(-7a + 2) + 10 = -6 + 8a

Reorder the terms:
4(2 + -7a) + 10 = -6 + 8a
(2 * 4 + -7a * 4) + 10 = -6 + 8a
(8 + -28a) + 10 = -6 + 8a

Reorder the terms:
8 + 10 + -28a = -6 + 8a

Combine like terms: 8 + 10 = 18
18 + -28a = -6 + 8a

Solving
18 + -28a = -6 + 8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8a' to each side of the equation.
18 + -28a + -8a = -6 + 8a + -8a

Combine like terms: -28a + -8a = -36a
18 + -36a = -6 + 8a + -8a

Combine like terms: 8a + -8a = 0
18 + -36a = -6 + 0
18 + -36a = -6

Add '-18' to each side of the equation.
18 + -18 + -36a = -6 + -18

Combine like terms: 18 + -18 = 0
0 + -36a = -6 + -18
-36a = -6 + -18

Combine like terms: -6 + -18 = -24
-36a = -24

Divide each side by '-36'.
a = 0.6666666667

Simplifying
a = 0.6666666667

See similar equations:

| 4(n+1)=(11-n) | | 6*8-(3-7)+8*3= | | w^2=54 | | 4(6)+(-6)=-24 | | inx=-3 | | 7=w+7/7+4w-3/5 | | a(6)-2(-6)=-12 | | 9=5n-1 | | 3-2x=4x+1 | | -93-10=8x+15 | | 3=39y | | 3x-2(2-2x-8)=72 | | k/3=8 | | -44-(-99)= | | 7(n-5)-(2-3n)=9n | | 96=6u | | 4y+3x=5fory | | 4-12y+9y^2=0 | | s-1=22 | | -1=10z-4 | | 1cx+qy=t | | k^2-11k+28=0 | | 81-18x+x^2=0 | | 85-3x=24x+22 | | 12+1/3a=2 | | -4(-2)(-1)(6)= | | 4x+12=9x-12 | | 3(2x-1)+3=4x | | X^2-5+1=0 | | -x+6=26 | | 6w(m-5)=108 | | 6y-5=25 |

Equations solver categories